2013
DOI: 10.1152/ajplung.00143.2012
|View full text |Cite
|
Sign up to set email alerts
|

Mucociliary transport in porcine trachea: differential effects of inhibiting chloride and bicarbonate secretion

Abstract: This study was designed to assess the relative importance of Cl(-) and HCO(3)(-) secretion to mucociliary transport rate (MCT) in ex vivo porcine tracheas. MCT was measured in one group of tissues that was exposed to adventitial HCO(3)(-)-free solution while a parallel group was exposed to adventitial HCO(3)(-)-replete solution. After measurement of baseline MCT rates, acetylcholine (ACh) was added to stimulate submucosal gland mucous liquid secretion, and MCT rates were again measured. Before ACh addition, th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

4
47
2

Year Published

2014
2014
2020
2020

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 51 publications
(54 citation statements)
references
References 48 publications
(120 reference statements)
4
47
2
Order By: Relevance
“…In the absence of bicarbonate, 3-month-old WT tracheae exhibited reduced pH of the airway surface, similar to the KO tracheae ( Figure 5A). Interestingly, the lack of bicarbonate transport did not change the solid content percentage ( Figure 5B) or PCL depth ( Figure 5C) in the 3-month-old WT rat tracheae; this is similar to the effects seen previously in pig tracheae treated with bicarbonate transport inhibitors (24,28,42,43) and is consistent at 1 and 6 months of age (data not shown). In contrast, the effects of absent bicarbonate on MCT rates recapitulated diminished transport in KO tracheae but only after gland maturation; in bicarbonate-depleted tracheae, MCT rates were reduced at 6 months under baseline conditions ( Figure 5D) and also at 3 and 6 months in cholinergically stimulated conditions ( Figure 5E).…”
Section: Resultssupporting
confidence: 88%
See 1 more Smart Citation
“…In the absence of bicarbonate, 3-month-old WT tracheae exhibited reduced pH of the airway surface, similar to the KO tracheae ( Figure 5A). Interestingly, the lack of bicarbonate transport did not change the solid content percentage ( Figure 5B) or PCL depth ( Figure 5C) in the 3-month-old WT rat tracheae; this is similar to the effects seen previously in pig tracheae treated with bicarbonate transport inhibitors (24,28,42,43) and is consistent at 1 and 6 months of age (data not shown). In contrast, the effects of absent bicarbonate on MCT rates recapitulated diminished transport in KO tracheae but only after gland maturation; in bicarbonate-depleted tracheae, MCT rates were reduced at 6 months under baseline conditions ( Figure 5D) and also at 3 and 6 months in cholinergically stimulated conditions ( Figure 5E).…”
Section: Resultssupporting
confidence: 88%
“…Previous studies, from our laboratory and others (12,24,42), have shown that bicarbonate secretion through the CFTR is critical for appropriate mucus transport. To determine whether this was true in the KO rat model and to test the relationship of this finding to mucus hydration, we conducted the same imaging experiments on WT tracheae in the presence and absence of bicarbonate and compared these to KO tracheae.…”
Section: Resultsmentioning
confidence: 80%
“…The CBF of CF piglets was lower compared with control piglets (5.4 6 0.9 Hz in CF vs. 10.6 6 1.5 Hz in non-CF, P , 0.05). Although unstimulated MCT of non-CF piglet was brisk (1.8 6 0.9 mm/min) and similar to measures of non-CF swine trachea made under physiologic conditions (24,35,36), CF MCT was severely delayed (0.2 6 0.1 mm/min, P , 0.05).…”
Section: Functional Anatomic Defects In Cftr (2/2) Piglet Tracheamentioning
confidence: 57%
“…Previous studies have demonstrated that thick airway mucus resembling the mucus observed in CF airways can be generated in genetically normal domestic pig tracheas in vitro by inhibiting active Cl − and HCO 3 − secretion in the presence of ACh, a stimulant of submucosal gland secretion (26,28). This model mimics the CF condition by greatly reducing Cl − /HCO 3 − and volume through the pharmacological inhibition of NKCC and NHE transporters in the basolateral membrane of epithelial secretory cells.…”
Section: Discussionmentioning
confidence: 96%